Identification of the Nicotianamine synthase (NAS) gene family in wheat (Triticum aestivum L.) and the role of its member TaNAS4-A in Zn and Fe transport - Gang Liu; Yixuan Sun; Pengyuan He; Yibo Wang; Yixuan Zhang; Qingfeng Li; Fenglou Liu; Shuangxi Zhang; Yingxia Zhang; Caixia Liu; Zhangjun Wang (Functional & Integrative Genomics, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Aggregation-induced emission photosensitizers for photodynamic food packaging: Antibacterial mechanisms, material innovations, and applications - Wenxin Wang; Shutian Sun; Simin Fan; Qingfeng Yang; Dequan Zhang; Chengli Hou (Trends in Food Science & Technology, 2026)

Combined effects of Chlorella application and reduced nitrogen fertilization on nitrogen use efficiency and crop yield in facility vegetable systems - Guoliang Zhao; Jingyu Sun; Xingcheng Hu; Zhengxi Cai; Chen Li; Qingfeng Chen (Applied Soil Ecology, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

SfIML-1 interacts with integrin β5 to mediate fungal conidial adhesion and immune activation in Spodoptera frugiperda - Fang-Fang Liu; Qi-Gui Gao; Yue Sun; Chao-Peng Liang; Hai-Yan Ren; Qingfeng Tang; Liang Wen; Bang-Xian Zhang; Xiang-Jun Rao (Pesticide Biochemistry and Physiology, 2026)

Fish-gill-inspired hierarchical membranes with charge-repulsion-mediated ion-selective nanostructures for enhanced desalination performance - Yingxue Zhang; Wei Sun; Haoyu Jiang; Qiuxuan Zhou; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2026)

Targeting the Wnt/β-catenin pathway: veratramine mitigates MNNG-induced gastric precancerous lesions - Pan Zhang; Xuelin Sun; Longteng Liu; Yatong Zhang; Jiaqi Bo; Wenli Huang; Yifan Na; Jingyi Zhang; Xiaoyun Qin; Qingfeng Luo (Molecular and Cellular Biochemistry, 2026)

Valorization of allelochemical-rich olive pomace: Comprehensive effect microbial nutrient release and ursolic acid-enhanced uptake improve crop growth and quality - Xisi Sun; Shuyang Wang; Fangzhu Guo; Junkai Wang; Guoqing Xiao; Qingfeng Wu; Yuhong Liu (Journal of Cleaner Production, 2026)

Contrasting response of the Asian Summer monsoon to bipolar climates and implications for ice core chronology during Marine Isotope Stages 5c-a inferred from stalagmite record, Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Yalan Zeng; Li Wu; Yijia Liang; Gongzhe Chen; Zhenqiu Zhang; Shaohua Yang; Chunsheng Hu; Peng Sun; Qingfeng Shao; et al. (Global and Planetary Change, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Study on the effects of ultraviolet inactivation in the process of gynogenetic development of grass carp eggs induced by mirror carp sperm - Wangchao He; Yu Sun; Kuo Chen; Junwen Liang; Binchao Liang; Xinyan Zhu; Qingfeng Liu; Yang Chen; Jialin Tang; Fuzhong Yang; Chun Zhang; Bo Chen; et al. (Aquaculture, 2026)

Chloride ions accelerated the removal of naproxen in Cu(II)/peracetic acid system: Promotion of copper cycling through the formation of copper-chloride complexes - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li (Water Research, 2026)

Enhanced removal of organic pollutants and effective suppression of chlorinated/brominated by-products in heat/peroxymonosulfate system by adding sodium percarbonate - Yao Huang; Chenyu Tang; Bingyu Lu; Jianhang Li; Lukai Zhuang; Minfeng Wang; Haoqiang Tan; Qingfeng Cheng; Qingsong Li; Bo Sun; Jing Zou (Journal of Environmental Chemical Engineering, 2026)

Effect of critical atomizing-flow distributor on thermal–hydraulic performance of finned evaporator - Zhili Sun; Jinjin Wang; Qifan Wang; Guanyuan Su; Qingfeng Bie; Yue Zhao; Jinfeng Chen; Hongyu Zhao; Zhan Wang; Xiaoyu Liu; Yihan Liu; Wenfu Zhang; et al. (International Journal of Refrigeration, 2026)

Interfacial engineering of graphene oxide with heterostructure to construct tortuous pathways in polylactic acid multilayers as barrier packaging - Qingfeng Yang; Xiaotong Sun; Dequan Zhang; Ming Tian; Wenxin Wang; Jinkai Pang; Xin Li; Wei Yang; Chengli Hou (Food Packaging and Shelf Life, 2026)

Effects of protein structure and proteomics on the moisture migration in rice with milling degrees - Jia Cao; Zeyu Peng; Lina Sun; Ruobing Jia; Bowen Yang; Jianjun Cheng; Qingfeng Ban; Huan Wang (Food Research International, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

High-performance, durable bamboo conductive macrofibers based triboelectric nanogenerator for stable harvesting water wave energy - Jiaqi Liao; Qingyu Meng; Wenwen Zhu; Wenhao Xu; Yang Peng; Shitao Shi; Zewei Ye; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2026)

An Adaptive Impedance Control Method for Underwater Dexterous Hands Based on Reinforcement Learning - Yuze Sun; Qingfeng Yao; Qiyan Tian; Naizhi He (Journal of Marine Science and Engineering, 2026)
With the continuous advancement of marine development, underwater operational tasks are becoming increasingly diverse and complex. Addressing the limitations of traditional methods and intelligent planning—which focus solely on acquiring task skills while separating grasp planning from force planning—this paper proposes a modeling approach integrating impedance control with deep reinforcement learning. Using a five-finger humanoid underwater dexterous hand as the grasping execution platform, this method achieves collaborative decision-making between grasp planning and force control for underwater dexterous hands. First, a modular underwater dexterous grasping scenario is established. Its kinematic model and inverse solution are analyzed, and the grasping problem is modeled as a Markov decision process. Second, based on the dexterous fingertip impedance control model for simulation, a grasping strategy learning method grounded in deep reinforcement learning is constructed to address the complex control challenges posed by the high degrees of freedom of the dexterous manipulator. Finally, the Proximal Policy Optimization (PPO) algorithm is employed for grasping strategy learning. An underwater dexterous grasping parallel training and testing environment is established using the Isaac Lab simulation platform to rapidly validate the learning method. Simulation results demonstrate the proposed method’s excellent dexterous compliant control performance and strong robustness to underwater variable environments: the PPO-based impedance control scheme reduces contact force variance by 56% compared to pure position control. The average maximum contact force is suppressed to 3.26 N, representing a 60.4% reduction compared to pure position control. This study achieves the organic integration of underwater hydrodynamic compensation, adaptive impedance control, and grasping strategy learning, providing a novel and effective solution for compliant grasping control of underwater dexterous manipulators.

Influence of varying oxygen transmission rates in heat-shrinkable packaging on the quality of beef during 90 days of chilled storage - Ming Tian; Jintao Jia; Dequan Zhang; Xiaotong Sun; Jiarui Li; Chaoqiao Zhu; Wei Yang; Xin Li; Qingfeng Yang; Chengli Hou (Meat Science, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

MnO2-resistant ABTS spectrophotometry for trace permanganate - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Xuewei Yu; Bo Sun; Zhongda Yan; Haoqiang Tan; Qingfeng Cheng; Jun Ma (ENGINEERING Environment, 2026)

Effects of anthropogenic activities on soil microbial communities and greenhouse gas fluxes in coastal wetlands of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Zihao Wang; Kun Li; Chenmiao Liu; Chen Li; Zhengxi Cai; Xinkun Zhao; Xinyi Xu; Hongjie Di; Qingfeng Chen (Journal of Environmental Sciences, 2026)

Low-amplitude structural features in the Baode Block, Ordos basin, China: Quantitative indicators, formation mechanisms, and coalbed methane implications - Fengfeng Du; Yanbin Yao; Yongchen Li; Qingfeng Zhang; Xiaoxiao Sun; Qiang Xu (International Journal of Coal Geology, 2026)

Texture-sweetness Co-design of dysphagia Foods:Research on the textural regulation and sweetener release mechanisms of soy protein gels by sucrose and xylitol - Yahui Du; Zengwang Guo; Chunfang Ma; Bolatkhan K. Zayadan; Qingfeng Ban; Hong Yang; Zhongjiang Wang; Hongbo Sun (Food Hydrocolloids, 2026)

Mechanically robust and flame-resistant cellulose nanofiber aerogels for efficient smoke pollutant adsorption - Yingying Li; Wenjie Xia; Caoxiong Zhuang; Hongfei Hu; Mingdi Kang; Huinan Wang; Lingling Zhu; Hanwei Wang; Qingfeng Sun (Carbohydrate Polymers, 2026)

Piezoelectric Analysis of a Hydrofoil Undergoing Vortex-Induced Vibration - Shiyan Sun; Yong Yang; Qingfeng Wang (Journal of Marine Science and Engineering, 2026)
This study numerically investigates the piezoelectric behavior of a hydrofoil under vortex-induced excitation. The fluid field, characterized by a Kármán vortex street forming around the hydrofoil, is solved using the finite volume method (FVM) based on viscous flow theory. The resulting vortex-induced pressure is then imported to compute the electric field by solving a coupled electromechanical problem within the finite element method (FEM) framework, which links the electric and strain fields. The temporal and spatial distribution of the voltage under the periodic excitation force is provided, and the affecting factors, including the attack angle and the flow velocity, are analyzed in detail.

Underlying mechanism and the effect of diacylglycerols on the protein structural stability and in vitro digestibility of pork meatballs - Xinxin Zhao; Yunling Jiang; Zixin Luo; Xiankun Sun; Jiangyu Zhu; Hai Yu; Xinyan Peng; Qingfeng Ge (Food Chemistry, 2026)

Facilitating redox cycles of copper species by peroxydisulfate in the copper-catalyzed Fenton-like system for enhanced oxidation of organic contaminants - Bingyu Lu; Jianying Wu; Chenyu Tang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li; Jun Ma (Water Research, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Bacterial communities of rhizolith- and root-associated in the Tengeri Desert, China - Jian Chen; Qingfeng Sun; Ruirui Chen; Zhihao Zhang; Zhen Liu; Gongyou Chen (Rhizosphere, 2025)

Dual-responsive carboxymethyl cellulose-based hydrogel sensor with antibacterial activity for wound monitoring and infected wound repair - Zhengjie Yu; Fanwei Zeng; Yuejin Cai; Zijie Wang; Ze Chen; Ruizi Wang; Qingfeng Sun; Xiaodong Tang; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

A carbon-negative aerogel with superior CO₂ capture, flame retardancy, and strength based on a cellulose/MOF three-dimensional network - Huinan Wang; Lingling Zhu; Wenjie Xia; Mingdi Kang; Qianqian Zhou; Weichen Shi; Xinyi Xiang; Qingfeng Sun; Yingying Li (Chemical Engineering Journal, 2025)

CoCA: Spatial cooperative simulation and future prediction of “land-population-economy” in urban agglomerations - Chenglong Zeng; Yao Yao; Jiayao Liu; Zhenhui Sun; Kun Zhou; Dongsheng Chen; Qingfeng Guan (Landscape and Urban Planning, 2025)

Multifunctional hydrogel-modified laminated wood for high-strength and fire-resistant structural applications - Zewei Ye; Haomeng Yu; Wenwen Zhu; Shitao Shi; Jiaqi Liao; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Corrigendum to “Investigating Hofmeister ions on rice starch gelatinization using simultaneous rheology and FTIR techniques combined with 2D correlation analysis” [Food Hydrocolloids 165 2025 111265] - Weijie Qi; Yaxing Xie; Lina Sun; Zhimo Jiang; Jianjun Cheng; Qingfeng Ban (Food Hydrocolloids, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Preparation of a high-strength, antibacterial, and biodegradable bio-based film through amide crosslinking and nano-reinforcement for fruit packaging - Shuguang Yang; Yile Xu; Anbo Pan; Peisheng Li; Wenwu Yang; Qingfeng Sun; Xiaochun Zhang; Yantao Xu (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Multi-factor analysis of enzyme activities under anthropogenic influence in the coastal wetland of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Xinkun Zhao; Qingfeng Chen (Journal of Environmental Management, 2025)

Smart eutectogel with antibacterial activity for efficiently treating multidrug resistant infection, real-time monitoring and diabetic wound repair - Zijie Wang; Baiwen Qi; Ruizi Wang; Ze Chen; Jingming Zhong; Zheng Wang; Qingfeng Sun; Aixi Yu; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

Investigating Hofmeister ions on rice starch gelatinization using simultaneous rheology and FTIR techniques combined with 2D correlation analysis - Weijie Qi; Yaxing Xie; Lina Sun; Zhimo Jiang; Jianjun Cheng; Qingfeng Ban (Food Hydrocolloids, 2025)

Mechanisms of plant-derived and microbial residue carbon in coastal wetland soils in response to salinity gradients - Xinkun Zhao; Jingyu Sun; Chenmiao Liu; Enyue Zhang; Guoliang Zhao; Qingfeng Chen (CATENA, 2025)

Using total Kalman filter to extract time-varying signals in PWV time series - Dantong Zhu; Kefei Zhang; Peng Sun; Suqin Wu; Qingfeng Hu; Peipei He; Weibo Yin; Yafei Wang; Junguo Liu (Advances in Space Research, 2025)

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Correction: Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Gels stability by improving the hydrophobic region of casein: Effect of the mogrosides on the structure, microstructure, and antioxidant activities in vitro digestive of the casein acid-induced gel - Yingdi Wang; Kun Sun; Yutong Hu; Yujie Lin; Jiaxuan Li; Qingfeng Ban; Fei Liu (Food Hydrocolloids, 2025)

Effects of anthropogenic activities on soil microbial community structure and methane anaerobic oxidation rate in coastal wetlands of Yellow River Delta, China - Chenmiao Liu; Zihao Wang; Xia Gao; Kun Li; Lei Yu; Jingyu Sun; Hongjie Di; Xiaoya Xu; Qingfeng Chen (Applied Soil Ecology, 2025)

Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Root Transcriptome of Wheat Genotypes Under Zinc Sufficient and Deficiency Conditions - Gang Liu; Ming Ma; Zhangjun Wang; Qingfeng Li; Fenglou Liu; Yixuan Sun; Shiping Hu; Caixia Liu (Journal of Plant Growth Regulation, 2025)

The formation and growth characteristics of an all-female hybrid crucian carp - Lujiao Duan; ChaoLiang Shen; Jingjing Lin; Xiaoxia Xiong; Huan Sun; Ziyi Huang; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Characterization of flavor profiles of water-boiled pork meatballs at different ultrasonic powers using solid-phase microextraction gas chromatography–mass spectrometry combined with electronic nose - Xinxin Zhao; Bangcheng Lai; Yunling Jiang; Xiankun Sun; Zixin Luo; Qingfeng Ge; Jiaxin Chen; Hai Yu (Meat Science, 2025)

Experimental Study on the Differences in Acoustic Emission Precursor Between Rockburst and Brittle Failure Based on the Data Mining Method - Jie Sun; Dongqiao Liu; Manchao He; Qingfeng Sun; Huili Huang (Rock Mechanics and Rock Engineering, 2025)

Effect of Borehole Pressure Relief on Rockburst: Insights from Borehole Cooperative Deformation Mechanism - Dongqiao Liu; Ziqian Zhang; Jinsong Yang; Qingfeng Sun; Zhengxi Liu; Jie Sun (Rock Mechanics and Rock Engineering, 2025)

MOFs meets wood: Renewable, self-supporting carbon-based composites for electromagnetic interference shielding with heat-resistant and electrothermal management - Yujun Rong; Xin Zhou; Shaohua Jiang; Wenkai Zhu; Hanwei Wang; Baokang Dang; Qingfeng Sun; Xiaofan Ma (Chemical Engineering Journal, 2025)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

Insighting the effect of lard-based diacylglycerol on the thermal gelation and rheological properties of myofibrillar protein influenced by soy protein isolate - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Mangang Wu; Qingfeng Ge; Xinyan Peng; Baohua Kong; Hai Yu (Food Hydrocolloids, 2024)

Hybrid chiral nanocellulose-cyanidin composite with pH and humidity response for visual inspection and real-time tracking of shrimp quality and freshness - Yingxuan Feng; Jian Lin; Xinjie Chen; Hao Chai; Linping Tian; Jiayi Zhang; Qingfeng Sun; Yushan Yang; Yingying Li (Food Chemistry, 2024)

Forces driving ecological degradation in southern China during the MIS3: Natural or anthropogenic? - Qiong Chen; Xiaobo Huang; Hua Tu; Qingfeng Shao; Xiaoming Sun; Qiaofen Liu; Wei Wang; Zhongping Lai; Xiaoqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

Applicability and sensitivity analysis of vector cellular automata model for land cover change - Yao Yao; Ying Jiang; Zhenhui Sun; Linlong Li; Dongsheng Chen; Kailu Xiong; Anning Dong; Tao Cheng; Haoyan Zhang; Xun Liang; Qingfeng Guan (Computers, Environment and Urban Systems, 2024)

Multiple thermal events recorded in the Acasta Gneiss Complex: Evidence from in-situ dating of zircon, titanite, and apatite - Qingfeng Mei; Jinhui Yang; Jinfeng Sun; Qiuli Li; Shitou Wu; Xiaoxiao Ling; Peng Peng; Hao Wang (Science China Earth Sciences, 2024)

Prevalence and distribution of antibiotic-resistant bacteria in the rhizosphere and rhizoplane of Suaeda salsa and Sporobolus alterniflorus grown in a pristine environment - Yu Wang; Fang Yang; Qianwen Liu; Lin Sun; Weihua Chen; Qingfeng Yu; Chenglong Pan; Guanhong Jiang; Xin'an Jiao; Yunzeng Zhang (Applied Soil Ecology, 2024)

Effects of ultrasound-assisted cooking on the physicochemical properties and microstructure of pork meatballs - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Meat Science, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Ultrastrong lightweight nanocellulose-based composite aerogels with robust superhydrophobicity and durable thermal insulation under extremely environment - Yushan Yang; Baokang Dang; Chao Wang; Yipeng Chen; Kaicong Chen; Xinjie Chen; Yingying Li; Qingfeng Sun (Carbohydrate Polymers, 2024)

The hind information: Exploring the impact of physical damage on mask microbial composition in the aquatic environment - Hu Wang; Zixian Zhu; Ling Zhang; Xiaohui Liu; Weihong Sun; Feifei Yan; Yuxin Zhou; Zhi Wang; Xiaofeng Wang; Chunyan Wei; Jie Lai; Qingfeng Chen; et al. (Environmental Research, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Temperature changes during the last deglaciation and early Holocene in southwest China - Weiwei Sun; Enlou Zhang; Qingfeng Jiang; Dongliang Ning; Wenlei Luo (Global and Planetary Change, 2023)

Boosting hydrogen evolution on MoS2 via synergistic regulation of interlayer dislocations and interlayer spacing - Longlu Wang; Feiran Zhang; Ning Sun; Lingbin Xie; Ting Zhi; Qingfeng Zhang; Zhongzhong Luo; Xia Liu; Shujuan Liu; Qiang Zhao (Chemical Engineering Journal, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Effect of high hydrostatic pressure on the edible quality, health and safety attributes of plant-based foods represented by cereals and legumes: a review - Yangyue Ding; Qingfeng Ban; Yue Wu; Yuxue Sun; Zhihao Zhou; Qi Wang; Jianjun Cheng; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Flexible and mechanically strong MXene/cellulose-lamellae sheets for electromagnetic interference shielding - Yushan Yang; Kaicong Chen; Baokang Dang; Chao Wang; Yipeng Chen; Ming Liu; Yingying Li; Xiaochun Zhang; Qingfeng Sun (Chemical Engineering Journal, 2023)

Portable smartphone-assisted ratiometric fluorescence sensor for visual detection of glucose - Xiaohui Zhang; Bo Sun; Yunyi Zhang; Qingfeng Zhang; Mahmood Hassan Akhtar; Ming Li; Yuwei Gu; Cong Yu (Analytica Chimica Acta, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

Enhanced remediation of phenanthrene in water and soil by novel biochar-immobilized bacterial microspheres - Kai Wang; Yang Sun; Dongyun Chen; Qingfeng Xu; Najun Li; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Anti-swellable cellulose hydrogel for underwater sensing - Zhuyue Lan; Yuanyuan Wang; Ke Hu; Shitao Shi; Qingyu Meng; Qingfeng Sun; Xiaoping Shen (Carbohydrate Polymers, 2023)

Carbonate cementing minerals in rhizoliths from Badain Jaran Desert: Implication for pedo-diagenesis and environment of dune soil - Qingfeng Sun; Kazem Zamanian; Arnaud Huguet; Guido L.B. Wiesenberg; Tianlei Zhao; Ziqiang Lei (Rhizosphere, 2023)

Heat-induced changes in epitopes and IgE binding capacity of soybean protein isolate - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Protein modification, IgE binding capacity, and functional properties of soybean protein upon conjugation with polyphenols - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

In-situ activities of anaerobic bacteria and methanogenic archaea in shallow lakes over the Anthropocene: A case study of Lake Wuliangsu - Yuxin He; Qingfeng Zhao; Dayang Sun; Huanye Wang (Chemical Geology, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Epoxy-functionalized polyethyleneimine modified epichlorohydrin-cross-linked cellulose aerogel as adsorbents for carbon dioxide capture - Xinjie Chen; Jian Lin; Hanwei Wang; Yushan Yang; Chao Wang; Qingfeng Sun; Xiaoping Shen; Yingying Li (Carbohydrate Polymers, 2023)

Genesis and soil environmental implications of intact in-situ rhizoliths in dunes of the Badain Jaran Desert, northwestern China - Qingfeng Sun; Kazem Zamanian; Arnaud Huguet; Omid Bayat; Hong Wang; Hanan S. Badawy (Acta Geochimica, 2022)
Desert rhizoliths are generally found as weathered, broken and scattered samples on dune field surface, but rarely in-situ in their initial states buried under the soil of desert in the Badain Jaran Desert, northwest China. This study offers an assessment of the morphological, mineralogical, and chemical properties of intact and in-situ rhizoliths found in soils of swales and depressions among dune chains. The characteristics of these rare and precious objects were assessed using optical polarizing microscopy, cathodoluminescence, scanning electronic microscopy, radiocarbon dating, and stable isotopic analyses, providing the opportunity for discussion of the rhizolith formation mechanisms and associated environmental conditions. Field and laboratory investigations showed that the in-situ intact rhizoliths were formed only in the places where Artemisia shrubs are living, and the remaining root relicts within rhizoliths belong to this species. The spatial distribution of rhizoliths also suggested that low topographic positions on a landscape provided soil moisture, and redox environments favored rhizolith formation. A semi-closed redox environment in the subsoil at swales and depressions, where water is always present, along with the sandy soil texture, facilitated fast water percolation to deeper depths and condensation. Such a soil environment not only provides water for Artemisia growth, but also for the weathering of minerals such as felspars and calcite from primary carbonates, and for the decomposition of root relicts. Furthermore, harsh climatic conditions, such as strong winds and solar radiation, led to water evaporation through dead root channels and triggered the calcification along the root relicts. The entrapped lithogenic carbonates and to a lesser extent the decomposition of Artemisia roots provided the carbon sources for the rhizoliths formation, while the weathering of soil minerals, particularly feldspars and carbonates, was the main source of Ca. Rhizoliths in the Badain Jaran desert formed relatively quickly, probably over a few soil drying episodes. This led to the entrapment of a large quantity of lithogenic carbonates (more than 90% of carbon) within rhizolith cement. The re-dissolution of the entrapped lithogenic carbonates in rhizolith tubes should be taken into account in the paleoenvironmental interpretation of 14 C ages, the latter suggesting that rhizoliths formed during the Holocene (~ 2053 years cal BP, based on root organic relicts).

High-Frequency Dependence of Acoustic Properties of Three Typical Sediments in the South China Sea - Jingqiang Wang; Zhengyu Hou; Guanbao Li; Guangming Kan; Baohua Liu; Xiangmei Meng; Qingfeng Hua; Lei Sun (Journal of Marine Science and Engineering, 2022)
The acoustic characteristics of three fine-grained sediments (silty sand, silt, silty clay) in the South China Sea (SCS) were measured and analyzed at high frequency range of 27–247 kHz. The measurement results show that the sound speed dispersion is a positive linear relation at the measured frequency range, and the attenuation follows nonlinear frequency dependence, α = kfn, where n ranges from 0.59 to 0.85 for the three different sediments in the SCS. The frequency dependence of sound speed and attenuation were compared with the published literature. It was found that for silty clay, clayey silt, silt, and silty sand, the dispersion characteristics of these four sediments are basically consistent; in general, the dispersion of coarse particles is significant, and that of fine particles is weak, and permeability is the key parameter that determines the inflection point of high frequency to low frequency. By modeling these sediments with the Biot–Stoll model, it was found that the Biot–Stoll model can better predict the frequency-dependent characteristics of sound attenuation in a high-frequency band under the matching constraints of sound speed dispersion characteristics, indicating that the Biot–Stoll model has good applicability to different types of sediments in a high-frequency band.

Late Cretaceous K-rich rhyolitic crystal tuffs from the Chuduoqu area in Eastern Qiangtang subterrane: evidence for crustal thickening of the central Tibetan Plateau prior to India–Asia collision - Yonggang Sun; Bile Li; Fengyue Sun; Qingfeng Ding; Junlin Dong; Ye Qian; Yujin Li; Zhen Yao (Acta Geochimica, 2022)

Late Jurassic adakitic ore-bearing granodiorite porphyry intrusions in the Xiaokele porphyry Cu (–Mo) deposit, Northeast China: implications for petrogenesis and tectonic setting - Yonggang Sun; Bile Li; Zhonghai Zhao; Qingfeng Ding; Fanbo Meng; Xusheng Chen; Ye Qian; Yujin Li (Acta Geochimica, 2021)

Soil and ambient air mercury as an indicator of coal-fired power plant emissions: a case study in North China - Zhonggen Li; Xufeng Chen; Wenli Liu; Taishan Li; Guangle Qiu; Haiyu Yan; Mingmeng Wang; Ji Chen; Guangyi Sun; Qingfeng Wang; Xinbin Feng (Environmental Science and Pollution Research, 2021)

Predicting the near-field strong ground motion based on uncertainties in asperities: an opportunity to reproduce the characteristics of the 1970 Tonghai earthquake (Ms 7.8) - Zongchao Li; Jize Sun; Xueliang Chen; Guochen Wang; Qingfeng Ding (Journal of Seismology, 2021)

Relationships between the sound speed ratio and physical properties of surface sediments in the South Yellow Sea - Guanbao Li; Jingqiang Wang; Xiangmei Meng; Baohua Liu; Guangming Kan; Guozhong Han; Qingfeng Hua; Yanliang Pei; Lei Sun (Acta Oceanologica Sinica, 2021)

The transcription factor VaNAC17 from grapevine (Vitis amurensis) enhances drought tolerance by modulating jasmonic acid biosynthesis in transgenic Arabidopsis - Lingye Su; Linchuan Fang; Zhenfei Zhu; Langlang Zhang; Xiaoming Sun; Yi Wang; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2020)

Overexpression of VaWRKY12, a transcription factor from Vitis amurensis with increased nuclear localization under low temperature, enhances cold tolerance of plants - Langlang Zhang; Tingting Zhao; Xiaoming Sun; Yi Wang; Chang Du; Zhenfei Zhu; Duncan Kiragu Gichuki; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Molecular Biology, 2019)

Oxymatrine improves L-arginine-induced acute pancreatitis related intestinal injury via regulating AKT/NFkB and claudins signaling - Hui Zang; Zhiqiang Zhang; Qingfeng Liu; Huimin Xiao; Tian Sun; Enling Guo; Lankun Zhang; Bensong Gong (Medicinal Chemistry Research, 2019)

Sound speed dispersion characteristics of three types of shallow sediments in the southern yellow sea - Guangming Kan; Baohua Liu; Jingqiang Wang; Xiangmei Meng; Guanbao Li; Qingfeng Hua; Lei Sun (Marine Georesources & Geotechnology, 2018)

Overexpression of VaWRKY14 increases drought tolerance in Arabidopsis by modulating the expression of stress-related genes - Langlang Zhang; Jun Cheng; Xiaoming Sun; Tingting Zhao; Mingjun Li; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2018)

Experimental study of the ballast in situ sediment acoustic measurement system in South China Sea - Jingqiang Wang; Guanbao Li; Baohua Liu; Guangming Kan; Zhiwen Sun; Xiangmei Meng; Qingfeng Hua (Marine Georesources & Geotechnology, 2018)

Preliminary studies of multi-micro/nanomaterials immobilized on the bamboo timber surface - Chunde Jin; Jingpeng Li; Jin Wang; Huanhuan Zheng; Qingfeng Sun; Shenjie Han; Chenye Yan; Qiufang Yao; Bitao Fan (Journal of the Indian Academy of Wood Science, 2016)

Construction of a recombinant Lactococcus lactis strain expressing a fusion protein of Omp22 and HpaA from Helicobacter pylori for oral vaccine development - Rongguang Zhang; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Qingtang Fan; Nan Sun; Yuanlin Xi (Biotechnology Letters, 2016)

Comparison of a fuzzy control and the data-driven model for flood forecasting - Yixiang Sun; Deshan Tang; Yifei Sun; Qingfeng Cui (Natural Hazards, 2016)

Chloroplast DNA-based genetic diversity and phylogeography of Pyrus betulaefolia (Rosaceae) in Northern China - Yu Zong; Ping Sun; Jing Liu; Xiaoyan Yue; Qingfeng Niu; Yuanwen Teng (Tree Genetics & Genomes, 2014)

Distribution of carbon and nitrogen in water-stable aggregates and soil stability under long-term manure application in solonetzic soils of the Songnen plain, northeast China - Qingfeng Meng; Yuting Sun; Jing Zhao; Lianren Zhou; Xianfa Ma; Meng Zhou; Wei Gao; Guangcheng Wang (Journal of Soils and Sediments, 2014)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Inhibition of focal adhesion kinase induces apoptosis in human gastric carcinoma cells (SGC-7901) - Jiyou Li; Qingfeng Meng; Yu Sun; Huadong Qing (Molecular Biology Reports, 2013)

Transgenic mice with overexpression of mutated human optineurin(E50K) in the retina - Qingfeng Meng; Zheng Xiao; Huiping Yuan; Fei Xue; Yuanmao Zhu; Xinrong Zhou; Binbin Yang; Jingbo Sun; Bo Meng; Xian Sun; Fang Cheng (Molecular Biology Reports, 2012)

A high-efficiency, two-dimensional gel electrophoresis platform for mature leaves of grass pea (Lathyrus sativus L.) - Qingfeng Wu; Chun Li; Lanming Ke; Chengjin Jiao; Jinglong Jiang; Xiaoyan Sun; Fengmin Li; Chongying Wang (Acta Physiologiae Plantarum, 2011)